2016
DOI: 10.1080/15374416.2016.1233500
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Randomized Controlled Trial of Omega-3 and Individual–Family Psychoeducational Psychotherapy for Children and Adolescents With Depression

Abstract: Objective Toevaluate feasibility and estimate effect sizes of omega-3 fatty acids (Ω3), individual-family psychoeducational psychotherapy (PEP), their combination, and moderating effects of maternal depression and psychosocial stressors in youth with depression. Method In a pilot 2X2 randomized controlled trial, 72 youth (ages 7-14; 57% Caucasian, 57% male) with major depression, dysthymia, or depression not-otherwise-specified were randomized to 12 weeks of Ω3, PEP+placebo, Ω3+PEP, or placebo. Ω3 vs. placeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 65 publications
0
57
1
1
Order By: Relevance
“…The participant sample was obtained from two NIMH-funded R34 studies (ClinicalTrials.gov identifiers: NCT01341925 NCT01507753), the goals of which were to determine feasibility and effects sizes for PUFA supplementation and family-focused, skills-based therapy for mood disorders [28, 29]. Secondary goals were to explore response curves over time, mediators and moderators, treatment response across a broad array of outcome variables, adherence to treatment, and side effects.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The participant sample was obtained from two NIMH-funded R34 studies (ClinicalTrials.gov identifiers: NCT01341925 NCT01507753), the goals of which were to determine feasibility and effects sizes for PUFA supplementation and family-focused, skills-based therapy for mood disorders [28, 29]. Secondary goals were to explore response curves over time, mediators and moderators, treatment response across a broad array of outcome variables, adherence to treatment, and side effects.…”
Section: Methodsmentioning
confidence: 99%
“…Only methods pertinent to the current analyses are described here; further details regarding recruitment and study design can be found elsewhere. [28, 29]…”
Section: Methodsmentioning
confidence: 99%
“…As previously reported by Fristad et al (2016), 69 of 72 participants from the depression trial had sufficient follow-up data to be included in LME analyses. These analyses indicated that while average CDRS-R scores decreased significantly over time for all treatment groups, no statistically significant group differences could be detected ( placebo alone, a small-medium effect (d s = 0.42) was detected for the Ω3 +AM group (Cohen, 1992), and a small effect was detected for Ω3 + IF-PEP (d s = 0.29).…”
Section: Nomothetic Approachmentioning
confidence: 94%
“…Participants in the first trial (n = 72; Fristad et al, 2016) were diagnosed with major depressive disorder (MDD), dysthymic disorder (DD), or depressive disorder not otherwise specified (D-NOS) using DSM-IV-TR criteria and were approximately 11.6 years old (SD = 2.1), 57% male, 57% Caucasian, and 10% Hispanic/Latino. Participants in the first trial (n = 72; Fristad et al, 2016) were diagnosed with major depressive disorder (MDD), dysthymic disorder (DD), or depressive disorder not otherwise specified (D-NOS) using DSM-IV-TR criteria and were approximately 11.6 years old (SD = 2.1), 57% male, 57% Caucasian, and 10% Hispanic/Latino.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation